Unsettling "Salidummay" a historico-ethnography of a music category - Reyes, Michiyo Yoneno (2011.)
This dissertation is a historico-ethnography of a musical category called "Salidumay", a cohort of folk songs that have been performed widely, although not evenly, in the northern Luzon highlands as well as outside region. This study asks how the musical category "salidumay" has been shaped, and how the villagers of northern Luzon highlands have been engaged with the notion of salidumay's traditionality. In so doing, it examines to performs salidumay?. Under what conditions? For what purposes? and With what results?
Thesis (Ph.D. Philippine Studies) -- University of the Philippines, Diliman.
Keywords: Ethnomusicology -- Philippines -- Sagada (Mountain Province).; Folk-songs, Philippine -- Sagada (Mountain Province).; Igorot (Philippine people) -- Music -- Philippines -- Sagada (Mountain Province).